Answer to Question #153561 in Math for muhammed alhabib

Question #153561

solve the D.E. y(n)-y(n-2)+y(n-3)=delta (n)


1
Expert's answer
2021-01-04T19:25:54-0500

"y[n]-y[n-2]+y[n-3]=\\delta[n]"

For, "x[n]=u[n]" ,

"D(z)=1-z^{-2}+z^{-3}=0\\\\\n\\Rightarrow z^3-z+1=0\\\\\n\\Rightarrow (z+1.32472)(z-0.66236 - 0.56228i)(z-0.66236 +0.56228i)=0\\\\\n\\Rightarrow z=0.66236 - 0.56228i=z_3 \\;\\;or,\\;\\; 0.66236 + 0.56228i=z_2\\\\\\;\\;or,\\;\\; 1.32472=z_1[let]"


"\\therefore" The solution :-


"y[n]=\\{c_1z_1^n+c_2z_2^n+c_3z_3^n+nc_1z_1^n+nc_2z_2^n+nc_3z_3^n+1)u[n]"


Where,

"z_1=1.32472\\\\\nz_2=z_3=0.66236+0.56228i\\\\z_3=0.66236-0.56228i"


Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be the first!

Leave a comment

LATEST TUTORIALS
New on Blog